2021
DOI: 10.1177/11207000211005750
|View full text |Cite
|
Sign up to set email alerts
|

Complications of primary total hip arthroplasty in human immunodeficiency virus-positive patients with femoral head osteonecrosis

Abstract: Background: Femoral head osteonecrosis (FHON) is a well-recognised complication in patients with human immunodeficiency virus (HIV) infection. Total hip arthroplasty (THA) is a reliable solution to FHON and has provided functional improvement and pain relief in these patients. Higher complication rates, in particular infections, have been reported in the series of THAs done in the HIV-positive patients. The purpose of this study was to evaluate the complication rate of THA for FHON in HIV-positive patients man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This study team from Dallas (Texas, USA) set out to establish what the outcomes were like for their cohort of 44 patients (56 arthroplasties) treated for FHON in the context of an HIV-positive diagnosis and HAART treatment. 7 As would be expected, the cohort was younger than the regular THA group, with an average age of 47 years and being predominantly male (n = 39/44). The authors reported that deep infection rate within the mean 6.6 years (2.0 to 11.3) of surveillance was lower than previously reported, with just two cases of deep periprosthetic infection.…”
Section: Total Hip Arthroplasty For Hiv Patients With Osteonecrosismentioning
confidence: 60%
See 1 more Smart Citation
“…This study team from Dallas (Texas, USA) set out to establish what the outcomes were like for their cohort of 44 patients (56 arthroplasties) treated for FHON in the context of an HIV-positive diagnosis and HAART treatment. 7 As would be expected, the cohort was younger than the regular THA group, with an average age of 47 years and being predominantly male (n = 39/44). The authors reported that deep infection rate within the mean 6.6 years (2.0 to 11.3) of surveillance was lower than previously reported, with just two cases of deep periprosthetic infection.…”
Section: Total Hip Arthroplasty For Hiv Patients With Osteonecrosismentioning
confidence: 60%
“…As therapies are getting better for HIV and patients are surviving for longer, out to normal life spans, the HIV-positive population is starting to suffer from a different range of problems. One 7 As would be expected, the cohort was younger than the regular THA group, with an average age of 47 years and being predominantly male (n = 39/44). The authors reported that deep infection rate within the mean 6.6 years (2.0 to 11.3) of surveillance was lower than previously reported, with just two cases of deep periprosthetic infection.…”
Section: Total Hip Arthroplasty For Hiv Patients With Osteonecrosismentioning
confidence: 68%
“…One of the postulated causes is the chronic use of antiretroviral drugs; however, it is unclear whether antiretroviral medication or the human immunodeficiency virus (HIV) itself is responsible for the pathogenesis of ONFH. 1 Despite the significant progress in the rollout of antiretroviral drugs, South Africa has one of the highest incidences of HIV globally. 2 We treat many patients with advanced bilateral ONFH (Steinberg stage IV-VI disease 3 ).…”
Section: Introductionmentioning
confidence: 99%